ANALYSIS OF THE SUPREME COURT DECISION NO. 119 PK/Pdt.Sus-HKI/2017 ON TRADEMARK DISPUTES FROM THE PERSPECTIVE OF HAQ AL-IBTIKAR - Muhammad Qeis; Muhammad Syuib; T. Surya Reza (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2026)
Trademark protection is an integral part of the intellectual property system that protects a product's reputation, economic value, and identity. According to Article 3 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, trademark protection is only granted to registered trademarks. However, in practice, trademark infringement has occurred, as in Supreme Court Decision Number 119 PK/Pdt.Sus-HKI/2017, between PT Gudang Garam as the owner of the well-known trademark